Genealogi Sekularisme Islam di Indonesia (1920–1945): Kontinuitas dan Perubahan Wacana - Indrawati (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
This research examines the genealogy of Islamic secularism in Indonesia in the period 1920–1945 with a focus on the background of the emergence, changes, and continuity of the discourse. This study uses Karl Mannheim's sociology of knowledge approach to trace the origins of Islamic secularist thought and Michel Foucault's archaeology of knowledge to analyze the dynamics of continuity and discontinuity of discourse over time. The results show that the discourse of Islamic secularism developed in three main periods. First, in the 1920s, the discourse of Islamic secularism began to emerge through Javanese nationalism. Second, in the period from 1930 to early 1945, nationalism developed by emphasizing love and willingness to make sacrifices for the country. Third, in 1945, the discourse of Islamic secularism grew stronger along with the establishment of the nation state and Pancasila as the basis of the state. This study shows a continuity in Islamic secularism in the form of a separation between politics and religion (Islam), as well as changes in the form of discourse that developed in each period. This finding contributes to the study of Islamic thought in Indonesia by highlighting the dynamics of secularism discourse in a broader socio-political context.